Meningkatkan Kualitas Pembelajaran Melalui Asesmen Efektif di Era Kurikulum 2013 - Nur Rahmadani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to explore the application of authentic assessment by Indonesian teachers at various levels of education (elementary, junior high, high school) in Indonesia. The main problems discussed are the lack of critical thinking skills development in students and the challenges in the implementation of authentic assessment in the context of daily learning. The research method used is a qualitative approach with case studies as the main focus. Data was collected through in-depth interviews, direct classroom observations, and analysis of documents such as Learning Implementation Plans (RPPs) and student portfolios. The results of the thematic analysis highlight general patterns, key themes, and conclusions related to the benefits, challenges, and strategies in implementing authentic assessments. This research is expected to provide in-depth insights into the effectiveness of authentic assessment in improving Indonesian learning in Indonesia.